Recent Publications (Quarterly Journal of Economics, 1957)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 71, Issue 3, August 1957, Pages 479–483, https://doi.org/10.1093/qje/71.3.479 Published: 01 August 1957